An Assessment of Program Sustainability in Three Bureau of Justice Assistance Criminal Justice Domains - Aharoni, Eyal (RAND Corporation, 2014)
Researchers examined the characteristics and environments of programs likely to persist beyond federal seed funding and to delineate strategies that will enable the Bureau of Justice Assistance to help programs sustain themselves. They assessed drug court, human trafficking, and mental health programs to identify factors associated with sustainment and recommend a plan for ongoing measurement of sustainability.